INTEGRITAS AKADEMIK DAN PENEGAKAN HUKUM PIDANA: MENGKAJI PENYALAHGUNAAN KEKUASAAN DAN DAMPAKNYA PADA TENAGA AKADEMIK UNIVERSITAS (Jurnal De Jure Muhammadiyah Cirebon, 2023)
The enforcement of criminal law in a fair justice system is an essential element to ensure social justice and respect for human rights. However, abuse of power in the law enforcement process can have far-reaching effects, including in academia. This research examines the relationship between academic integrity and the potential for abuse of power in criminal law enforcement, and its impact on the performance of academic personnel at universities. In this context, abuse of power refers to unfair or arbitrary actions by law enforcement in handling criminal cases that can affect the atmosphere of academic freedom, professionalism and objectivity in higher education. This research aims to explore how injustice in law enforcement can disrupt the performance of academic personnel, create uncertainty, and reduce trust in the legal system. Using a qualitative approach, this study identifies the impacts that can arise in the interaction between criminal law and higher education institutions, and provides recommendations to strengthen academic integrity in the face of potential abuse of power